2011 18th IEEE International Conference on Image Processing 2011
DOI: 10.1109/icip.2011.6115788
|View full text |Cite
|
Sign up to set email alerts
|

Removing shadows from images using color and near-infrared

Abstract: Shadows often introduce errors in the performance of computer vision algorithms, such as object detection and tracking. This paper proposes a method to remove shadows from real images based on a probability shadow map. The probability shadow map identifies how much light is impinging on a surface. The lightness of shadowed regions in an image is increased and then the color of that part of the surface is corrected so that it matches the lit part of the surface. The result is compared with two other shadow remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…We found that the depth variance is higher than predicted for i −2 ∈ [1, 39], which corresponds approximately to i ∈ [0. 16,1]. In this intensity interval we observed an increase in the intensity variance as well.…”
Section: Camera Noise Modelsupporting
confidence: 49%
See 1 more Smart Citation
“…We found that the depth variance is higher than predicted for i −2 ∈ [1, 39], which corresponds approximately to i ∈ [0. 16,1]. In this intensity interval we observed an increase in the intensity variance as well.…”
Section: Camera Noise Modelsupporting
confidence: 49%
“…Salamati et al [16] propose to capture a color and an infrared image to detect and remove shadows. However they use no active infrared illumination, but capture the ambient infrared light.…”
Section: Related Workmentioning
confidence: 99%
“…In [3] the authors have developed a method to remove the shadows from real images based on probability shadow map. The probability shadow map identifies the amount of shadow that is affecting the surface.…”
Section: Related Workmentioning
confidence: 99%
“…Removing shadows from image is effective in simplifying the tasks of image processing and computer vision algorithms. However, removing the shadow has to maintain the information in the original image and the other details except the shadow [3].…”
Section: Introductionmentioning
confidence: 99%
“…Differences of light and scene reflections in the visible part of the electromagnetic spectrum (with wavelengths of 400-700 nm) and the NIR band (wavelength range of approximately 700-1100 nm) inspired researchers to use NIR information along with color images in tasks that are traditionally performed using color information only. Some of these applications are image denoising, 1 image dehazing, 2 shadow detection and removal, 3,4 and video conference relighting.…”
Section: Introductionmentioning
confidence: 99%